(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
In this article, in the conditions of the meadow gray soils of the Jizzakh region, in the care of the non-traditional leguminous crop crotalaria (Crotalaria juncea L.), when using Geogumat biostimulator at the rate of 1.0 l/t and 1.6 l/ha in the 3-4 true leaves and branching periods, with the number of leaves in the main plant being 336.0 pieces, the area of the upper leaf surface is 1517.9 cm2, compared to the control option, 179.8 cm2; 117.4 cm2 compared to the option of using Uzgumi biostimulant only with planting; It was stated that the photosynthetic productivity increased by 72.2 cm2 compared to the variant used only with planting.